THE TEMPLAR SECRET - Mariani, Scott (Manchester, England : Harper North, 2024)
A set of symbols scratched on the wall of a crypt in southern France. A flag bearing a red cross on a castle fortress high on a stone ledge. And deep in the heart of the Vatican, a team of agents charged with making sure no one discovers what connects them all. Ben Hope is a magnet for trouble. Years since leaving the SAS, he can still feel when danger is stalking him. But stumbling across someone researching the Knights Templar seems like a problem for historians rather than his military skills. It's only when a terrible twist of fate puts not just Ben but the people he loves in the firing line that he realises the battles of the past will soon wreak carnage in the present. Faced with uncovering a mystery that strikes at the heart of Western civilisation, Ben might finally have unearthed the one secret that could take him down.
Keywords: Veterans -- Fiction; Crypts -- Fiction; Conspiracies -- Fiction; Secrecy -- Fiction; Action and adventure fiction; Thrillers (Fiction)